The Recognition of the Dolgans, Science and Soviet Institutions’ Toil - Borjon-Privé, Yann (HAL CCSD, 2021)
International audience This article is on the recognition of the Dolgans as an official nationality in the USSR. Sometimes, scholars consider that the Dolgan people appear between the second half of the 19th century and the 1960’s. What does it mean? How can a people appear? Are the Dolgan people a creation of Soviet administration? Or were they a forgotten people? Cet article porte sur la reconnaissance des Dolganes comme une nationalité officielle en URSS. Parfois, des académiciens considèrent que le peuple dolgane est apparu entre la seconde moitié du XIXe siècle et les années 1960. Que signifie ce point-de-vue ? Comment un peuple peut-il apparaître ? Le peuple dolgane a-t-il été créé par l'administration soviétique ? Ou était-ce un peuple oublié ?